Public Policy Discourse Debate: Discourse Network Analysis The "One Person, One Social Media Account" Issue in Indonesian Online Media - Maria Theresia Efika Rosemarie (Eduvest - Journal of Universal Studies, 2026)
The proliferation of fake and anonymous accounts on social media has prompted the Indonesian government to propose a controversial “One Person, One Social Media Account” policy. This study aims to map the actors, concepts, and discourse coalitions that emerge in the public debate surrounding this policy proposal. Utilizing Discourse Network Analysis (DNA), this research analyzes 81 online news articles published between July and September 2025. The analysis identifies key actors, their stated concepts, and the network structures formed through their agreement or disagreement on the issue. The results reveal a highly structured and dominant pro-policy coalition, primarily comprising members of the House of Representatives (DPR) and the Ministry of Communication and Digital (Komdigi). These actors exhibit the highest network centrality and articulate a cohesive narrative centered on concepts such as “account restrictions prevent anonymous/fake accounts” and “prevent hoaxes.” In contrast, the counter-policy discourse—featuring concepts such as “prioritize digital literacy” and primarily voiced by academics and activists—is notably weaker, fragmented, and peripheral within the network. The study concludes that the institutional power of pro-policy actors, combined with their compelling security-focused narrative, has produced a dominant discourse coalition. These findings provide both methodological and empirical contributions to understanding the dynamics of public policy discourse formation in Indonesia’s digital era